Penerapan Relaksasi Benson terhadap Kadar Gula Darah pada Pasien Diabetes Militus di Ruang Seroja RSUD Limpung - Desfiyanti Dewi Anggraeni; Arifianto Arifianto (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Type 2 diabetes mellitus is a chronic metabolic disease characterized by elevated blood glucose levels due to impaired insulin secretion and insulin resistance. This study aimed to analyze the effect of Benson relaxation on random blood glucose levels in patients with type 2 diabetes mellitus at the Seroja Ward of Limpung Regional General Hospital. The method used was a quasi-experimental study with a one-group pretest–posttest design involving four respondents selected via purposive sampling. The Benson relaxation intervention was conducted for 15–20 minutes once daily over three consecutive days, accompanied by blood glucose measurements before and after the intervention using a glucometer. The results showed a decrease in blood glucose levels in all participants with individual variations in response, where the most stable decrease occurred in participants with better lifestyle control. Benson relaxation works by reducing stress and activating the parasympathetic nervous system, which contributes to increased insulin sensitivity. In conclusion, Benson relaxation is effective as a supportive nonpharmacological therapy in controlling blood glucose levels in patients with type 2 diabetes mellitus.